ANALISIS NILAI PENDIDIKAN DAN GAYA BAHASA DALAM NOVEL AYAHKU (BUKAN) PEMBOHONG KARYA TERE LIYE - Ni Komang Ayu Wintari; Ni Luh Sukanadi (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2021)
This research is a descriptive studi aimed at describing (1) the structure that builds my father’s novel (not) Liar by Tere Liye, (2) the educational value in my father’s novel (not) Liar by Tere Liye’s work (3) Language stlye in my father’s novel (not) Liar Tere Liye’s . The method use is qualitative descriptive. The object of study is the educational value and language stly in my father’s novel (not) liar. This research data in the from of words, phrases, sentences, and discourse that contain educational value and language stlyes in the novel father’s not liar. Data collection techniques used were observation and literature. Based on the results of this study are. Based on an analysis of the value of education in the novel my father is not a lair namely, a) honest, b) independent, c) hard work, d) responsibility, e) fond of reading, f) curiosity, g) discipline, h) respect achievement, i) friendly or communicative, j) social care, and k) tolerance. In addition there are also various styles of language used by the author in my father’s novel (not) a liar by namely, a) Equality or simile, b) personification, c) metaphor, d) irony, and e) hyperbole.